Islamic Human Development and Corruption Control: Evidence on Poverty in OIC Countries - Thariq Abdurrabbi; Filzah Wafiyah; Tika Widiastuti (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Poverty remains a persistent challenge across many member countries of the Organization of Islamic Cooperation (OIC). This study examines the effects of Islamic human development and corruption control on poverty in OIC countries. Using panel data regression with a Fixed Effects Model (FEM), the study analyses secondary data from nine selected OIC member countries over the period 2011–2023. The findings show that the Aql and Maal dimensions significantly affect poverty, although the direction of their effects differs. Aql has a positive relationship with poverty, whereas Maal contributes to poverty reduction. Rule of Law, Regulatory Quality, Government Effectiveness, and Political Stability also significantly contribute to reducing poverty. In contrast, the Diin, Nafs, and Nasl dimensions show no statistically significant effects. The general Control of Corruption indicator is also insignificant, suggesting that specific governance dimensions provide greater explanatory power for poverty than aggregate corruption control. These findings highlight the importance of strengthening Maqasid Syariah based human development and institutional governance as key components of poverty alleviation strategies in OIC countries.